2007
DOI: 10.1007/s10620-007-9841-1
|View full text |Cite
|
Sign up to set email alerts
|

12-Lipoxygenase Induces Apoptosis of Human Gastric Cancer AGS Cells via the ERK1/2 Signal Pathway

Abstract: 12-Lipoxygenase (12-LOX) is over-expressed in a variety of human tumors, but its exact effect on the tumorogenesis of gastric cancer remains largely obscure. To investigate the effect of 12-LOX and its inhibitor baicalein on proliferation and apoptosis of human gastric cancer, AGS cells were separately treated with 12-hydroxyeicosatetraenoic acid (12-HETE, a metabolite of 12-LOX) and baicalein. MTT assay revealed that the absorbance of the 12-HETE-treated group was significantly (P < 0.01) higher than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…12-LOX and its metabolites have been shown to promote cancer progression and metastasis through a MAPK-dependent pathway (Szekeres et al, 2000;Ding et al, 2001). Inhibition of 12-LOX in tumor cells was shown to induce apoptosis and was blocked by either overexpression of 12-LOX or addition of 12-HETE (Szekeres et al, 2000;Chen et al, 2008). In platelets, however, the underlying signaling mechanisms regulating 12-LOX-mediated platelet reactivity have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…12-LOX and its metabolites have been shown to promote cancer progression and metastasis through a MAPK-dependent pathway (Szekeres et al, 2000;Ding et al, 2001). Inhibition of 12-LOX in tumor cells was shown to induce apoptosis and was blocked by either overexpression of 12-LOX or addition of 12-HETE (Szekeres et al, 2000;Chen et al, 2008). In platelets, however, the underlying signaling mechanisms regulating 12-LOX-mediated platelet reactivity have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…12-LO has been repeatedly implicated in carcinogenesis (55)(56)(57), atherosclerosis (58)(59)(60), hypertension (61,62), and stroke (63,64). Increased biosynthesis of 12(S)-HPETE, the major 12-LO product of AA oxygenation, led, for example, to upregulation of protein kinase C-a via a receptor-mediated mechanism (65) and NF-k-B (66) in certain types of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…involvement of the lOx pathway in cancer, including breast cancer, has been reported, and studies have unequivocally shown a link between the lOx pathway and cancer. up-regulated expression of lOxs has been determined in both animal models of cancer (32) and in humans (7,30). Jiang et al (36) and mohammad et al (37) showed increased levels of alOx12 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have implicated alOxs and their products in various pathologies linked with inflammation, including Alzheimer's disease (23,24), atherosclerosis (25,26), hypertension (27), stroke (27)(28)(29) and cancer (7). Evidence links up-regulated alOx12 expression to the development of cancer, sustenance, growth and metastasis (11,(30)(31)(32)(33)(34). Overexpression of alOx12 has been demonstrated in various types of cancers, including breast, renal, pancreatic and prostate (13,(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%